Finance, infrastructure and urban capital: the political economy of African 'gap-filling'. Issue 164 (2nd April 2020) - Goodfellow, Tom
ABSTRACT: Financial flows into Africa are being reoriented through the pervasive discourse of the 'infrastructure gap'. The article argues that the generation of new infrastructures identified as 'alternative assets' by global finance is also creating landscapes of opportunity for urban capital accumulation by more locally embedded actors. Thus, as international financial flows are becoming 'infrastructuralised', domestic capital is increasingly 'real-estatised'. The conceptualisation of African urban economies in terms of deficits has obscured the extent to which they are also characterised by surfeits, including of certain kinds of property development and speculation, with important implications for the politics of urban accumulation, dispossession and violence.